Fluid reasoning and reading difficulties among children with ADHD. Issue 4 (2nd October 2019) - Mano, Quintino R.; Jastrowski Mano, Kristen E.; Guerin, Julia M.; Gibler, Robert C.; Becker, Stephen P.; Denton, Carolyn A.; Epstein, Jeffery N.; Tamm, Leanne
Abstract: Background: Children with attention-deficit/hyperactivity disorder (ADHD) commonly experience difficulties in reading and in fluid reasoning (G f ). According to Cattell's Investment Theory (1987), G f is a causal factor in the development of crystallized knowledge (G c ) and academic skills; therefore, the co-occurrence of reading and G f difficulties within ADHD may not be coincidental. Methods: In the present study with children with both ADHD and reading difficulties ( n = 187; 61% male; Mage = 9.2), we utilized mediation analyses to test direct and indirect (through G c, phonemic awareness, and rapid automatized naming [RAN]) effects of G f on four basic reading skills: untimed word recognition, untimed phonemic decoding, word reading efficiency, and phonemic decoding efficiency. Results: The direct effect of G f on all reading skills was nonsignificant; however, significant indirect effects were observed. Specifically, G f exerted an effect indirectly onto all reading skills through a serial and joint mechanism comprised of G c and phonemic awareness (i.e., G f → G c → phonemic awareness → reading achievement). G f also exerted an effect indirectly onto untimed word recognition and phonemic decoding through phonemic awareness (i.e., G f → phonemic awareness → untimed word recognition/untimed phonemic decoding). Conclusion: Results build upon Cattell's Investment Theory by linking G f with reading difficulties among children with ADHD, suggesting that such difficulties may arise from weaknesses in G f and insufficient investment of G f into reading through G c and phonemic awareness.